Biowaste valorization for emerging pollutant abatement in aqueous phase - Lago, Ana Elisa Marques (2022)
The use of raw chemical- or thermal-modified pine bark (10 g/L) as a biosorbent to remove fluoxetine hydrochloride (FLX), carbamazepine (CRB) and atrazine (ATZ) from water at 5 mg/L each was explored in this work. The adsorption efficiency onto raw pine was as follows: FLX > ATZ > CRB. Pine oxidized with HNO3 revealed to be the best modified biosorbent in terms of overall sorbate entrapment capacity (1.95 mg/g). The performance of raw pine (as the most sustainable biosorbent) was assessed in a prepilot air-lift-type reactor as a rehabilitation system to treat contaminated water for upscale purposes.